Pengaruh Jenis Eksplan dan Komposisi Media terhadap Pembentukan Tunas Tanaman Karet (Hevea brasiliensis Muell. Arg.) Secara In Vitro - Emmy Rosita; Luthfi Aziz Mahmud Siregar; Emmy Harso Kardhinata (Universitas Sumatera Utara, 2016)
The aim of this research is to evaluate the influence of medium composition and types of explant on shoot formation of rubber tree (H. brasiliensis Muell. Arg.). The research was carried out in the In Vitro Culture Laboratory, PT. Perkebunan Nusantara III Kebun Gunung Pamela, Tebing Tinggi, Sumatera Utara, Indonesia. The research was conducted from March to July 2015. The research was arranged in completely randomized design with two factors, i.e.: types of explant and the medium with combination of growth regulatorsand fifteen replications. The results showed that interaction types of explant and medium with combination of growth regulators gave significant effect on percent of shoots.Key words: rubber, multiplication, explants, medium in vitroThe aim of this research is to evaluate the influence of medium composition and types of explant on shoot formation of rubber tree (H. brasiliensis Muell. Arg.). The research was carried out in the In Vitro Culture Laboratory, PT. Perkebunan Nusantara III Kebun Gunung Pamela, Tebing Tinggi, Sumatera Utara, Indonesia. The research was conducted from March to July 2015. The research was arranged in completely randomized design with two factors, i.e.: types of explant and the medium with combination of growth regulatorsand fifteen replications. The results showed that interaction types of explant and medium with combination of growth regulators gave significant effect on percent of shoots.Key words: rubber, multiplication, explants, medium in vitro